Frozen, chilled and spray dried emulsions for whipped cream: Influence of emulsion preservation approaches on product functionality. Issue 1 (June 2015) - Zhao, Qiangzhong; Kuang, Wanmei; Fang, Min; Sun-Waterhouse, Dongxiao; Liu, Tongxun; Long, Zhao; Zhao, Mouming
Abstract: This study compares the effect of frozen (−18 °C) or chilled (4 °C) storage, or spray drying approach of emulsion on the physico-chemical, whipping and rheological properties of the resultant whipped creams and/or their emulsions. The average particle size and apparent viscosity of spray dried emulsion were significantly ( p < 0.05) larger than those of frozen and chilled emulsions. The microstructural difference was well correlated with the measured changes of particle size distribution. The flow curves of these emulsions were best fitted with the Herschel-Bulkley model, showing pseudoplasticity. The partial coalescence of fat droplets in powdered whipped cream (PWC) increased much slowly than other emulsions, while whipped cream from chilled emulsion (CWC) exhibited greater partial coalescence of fat than whipped cream from frozen emulsion (FWC) during whipping. Significant differences ( p < 0.05) of whipped cream under different processing (frozen or chilled storage and spray drying) were also observed in yield stress, creep behavior and overrun. Highlights: Particle size of spray dried emulsion increased significantly ( p < 0.05). Chilled emulsion showed a higher partial fat coalescence than frozen emulsion. Powdered whipped cream exhibited longer retardation time in creep test.